SUSHRUTA’S GENERAL PRINCIPLES OF FRACTURE CARE TREATMENT & MANAGEMENT (AYUSHDHARA, 2016)
Orthopedic conditions are well explained and documented in the literature of Ayurveda in the name of “Bhagna Chikitsa”. Many of the new techniques are developed for the management as per the condition. Acharya Sushruta described exclusively about fracture, its etiology, classification and various modalities of the management. Bhagna in ancient period were commonly encountered problem occurs in wars and attacks by animals etc but in the present time these are commonly as a result of RTA. Bhagna was explained by Acharaya Sushruta depending upon nature of trauma, shape of fracture, displacement of fracture fragments and fracture with or without wound. If it occurs in the bone it is called as Kand bhagna (bone fracture) and in the joint it is called as Sandhimoksha (dislocation). The principle of fracture management defined by Acharya Sushruta centuries ago are as per condition suggests conservative or surgical treatment. Conservative modalities includes Kushabandha, Alepa, Chakrayoga, Taila Droni, etc are still relevant. The western medicines takes over in the management of complicated fractures with the introduction of many surgical instruments like the intramedullary nails, etc & delays fracture union and healing potential. This paper expounds the wisdom of orthopedic branch in ancient times especially fracture & its management with possible modern correlation and how much knowledge existed and how well organized was it so many centuries ago. It would be worthwhile to explore these unique features for use in present times. The concepts, theories and techniques practiced several thousand years ago hold true even in today’s modern era.